Assessing the distributional effects of housing taxation in Italy: From the actual tax code to imputed rent - Simone Pellegrino; Massimiliano Piacenza; Gilberto Turati (Center for Economic Studies and ifo Institute (CESifo), 2011)
The presence of extensive housing subsidies characterises the current tax systems as inefficient. In this paper, we study whether inefficiency is the price to be paid to improve equity, by assessing the actual distributive impact of housing taxation on Italian households. We concentrate on the personal income tax on the main residence, and compare provisions of the Tax Code with an alternative approach, by considering the imputed rent from owner-occupied dwelling as a component of the Personal Income Tax gross income. Our results suggest that current tax system is just as inefficient as it is inequitable.
Keywords: H24; D31; 330; housing taxation; imputed rents; microsimulation models; Grundsteuer; Steuerinzidenz; Einkommensteuer; Verteilungswirkung; Bodenrente; Kalkulatorische Kosten; Italien